Design and Social Innovation at the Margins: Finding and Making Cultures of Plurality. (2nd January 2019) - Light, Ann
Abstract: Design has become a global activity dominated by one set of cultural interests to produce a consistency of practice. This essay uses an experience of design for social innovation in northern Finland, inspired by land and place, to speculate upon the dimensions across which plurality in designing could be embraced in an increasingly globalized world. Informed by discussions while helping to run the Design and Social Innovation in Asia-Pacific events of 2016, it uses Kasulis' analysis of cultural orientation and his insight that a key difference underpinning cultures is how people may orientate towards intimacy and integrity. It then explores what a form of intimate design might look like. In doing so, it uses Ingold's study of North-ness to challenge totalizing narratives of progress and explore what a marginal view can offer to address site-specific needs and dispense with design orthodoxies.